2016
DOI: 10.7863/ultra.15.02064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carpal Tunnel Syndrome on the Ulnar Nerve at the Wrist

Abstract: The cross-sectional areas of the ulnar and median nerves at the wrist are increased in patients with carpal tunnel syndrome. Also, the cross-sectional area of the ulnar nerve is decreased after carpal tunnel release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…We also found a correlation between the sensory recordings on the ulnar nerve on the ring finger and CTS aggravation, disability, and risk factors, which supports other studies evidencing common moderate involvement of the ulnar nerve in the clinical presentations of CTS ( 132 , 133 , 134 , 135 , 136 , 137 , 138 ) or that computer work is associated with the ulnar nerve entrapment at the elbow (cubital tunnel syndrome) and the wrist (Guyon's canal syndrome) due to repetitive compression from leaning on the elbows or wrists during work with a mouse or a keyboard ( 139 , 140 , 141 ).…”
Section: Discussionsupporting
confidence: 89%
“…We also found a correlation between the sensory recordings on the ulnar nerve on the ring finger and CTS aggravation, disability, and risk factors, which supports other studies evidencing common moderate involvement of the ulnar nerve in the clinical presentations of CTS ( 132 , 133 , 134 , 135 , 136 , 137 , 138 ) or that computer work is associated with the ulnar nerve entrapment at the elbow (cubital tunnel syndrome) and the wrist (Guyon's canal syndrome) due to repetitive compression from leaning on the elbows or wrists during work with a mouse or a keyboard ( 139 , 140 , 141 ).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have shown that patients with CTS may have UN damage [ 16 , 17 ]. A study by Kang et al found that when patients with CTS underwent carpal tunnel release, the pressure in Guyon’s canal was reduced and the sensory conduction of the UN improved [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that patients with CTS may have UN damage [ 16 , 17 ]. A study by Kang et al found that when patients with CTS underwent carpal tunnel release, the pressure in Guyon’s canal was reduced and the sensory conduction of the UN improved [ 16 ]. However, in several studies with larger patient populations, UN conduction was found to be unaffected in patients with CTS [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For antenna arrays, the effect of mutual coupling can be evaluated straightforwardly thanks to the fact that each element can be fed separately. Techniques like mutual admittance matrix or incremental impedance are usually used to compensate the mutual coupling effects [9][10].…”
Section: Emperical Modelization Of Short Crlh Lwamentioning
confidence: 99%